A High‐Throughput Approach to Repurposing Olefin Polymerization Catalysts for Polymer Upcycling. (5th April 2022) - Cannavacciuolo, Felicia D.; Yadav, Rinku; Esper, Alec; Vittoria, Antonio; Antinucci, Giuseppe; Zaccaria, Francesco; Cipullo, Roberta; Budzelaar, Peter H. M.; Busico, Vincenzo; Goryunov, Georgy P.; Uborsky, Dmitry V.; Voskoboynikov, Alexander Z.; et al.
Abstract: Efficient and economical plastic waste upcycling relies on the development of catalysts capable of polymer degradation. A systematic high‐throughput screening of twenty‐eight polymerization catalyst precursors, belonging to the catalyst families of metallocenes, ansa ‐metallocenes, and hemi‐ and post‐metallocenes, in cis ‐1, 4‐polybutadiene (PB) degradation reveals, for the first time, important structure–activity correlations. The upcycling conditions involve activation of the catalysts (at 0.18 % catalyst loading) with tri‐ iso ‐butyl aluminum at 50 °C in toluene. The data indicate the ability to degrade PB is a general reactivity profile of neutral group 4 metal hydrides. A simple quantitative‐structure activity relationship (QSAR) model utilizing two descriptors for the distribution of steric bulk in the active pocket and one measuring the metal ion electrophilicity reveals the degradation ability improves with increased but not overbearing steric congestion and lower electrophilicity. Abstract : Over the past half‐century thousands of early metal precatalyst derivatives have been created for polyolefin synthesis. These same catalysts, under the appropriate conditions have potential to degrade polymers. The large number of precatalysts available requires a high‐throughput approach to accelerate discovery. Herein, we present the discovery of several active catalysts for the degradation of polybutadiene using high‐throughput.